Effects of nucleotides administration on growth performance and immune response of post-weaning piglets. Issue 1 (14th December 2020) - Perricone, Vera; Comi, Marcello; Bontempo, Valentino; Lecchi, Cristina; Ceciliani, Fabrizio; Crestani, Maurizio; Ferrari, Alessandra; Savoini, Giovanni; Agazzi, Alessandro
Abstract: The aim of this study was to assess the effect of nucleotides administration on growth performance and immune response in post-weaning piglets. Twenty-eight male weaned piglets, homogeneous for age and weight were randomly allocated to two experimental treatments. Treated group (T) was daily orally administered 0.8 g/head of a mixture of nucleotides suspended in 2.1 mL water solution; while control group (C) received 2.1 mL saline solution. Body weight (BW) and average daily gain (ADG) were individually recorded weekly, while feed intake (FI), and gain:feed (G:F) were recorded and calculated on pen basis. Faecal score was evaluated every seven days. On day 0, 9, 18 and 27 blood samples were collected to determine IgA, IgG and haptoglobin concentration. At day 28 all piglets were sacrificed, and tissue samples of ileal Peyer's patches were collected for the evaluation of IL1α, IL1β, IL6, IL10, TNFα, TLR2, TLR4 and PPARγ gene expression. Nucleotides supplementation significantly increased BW (17.37 vs. 19.00 kg/pig; p = <.01), ADG (.351 vs. .400 kg/d; p < .01), and FI (3.96 vs. 4.39 kg/d; p < .01), but not G:F (.61 vs. .64; p = .29). Faecal consistency was not different between the experimental groups and no occurrence of diarrhoea was reported. IgA and IgG content in blood was not influenced by the treatment, as well as gene expression of inflammatory cytokines in Peyer's patches. The present trial shows that nucleotide administration is able to improve growth performance of post-weaning piglets, with no effects on inflammatory response and the expression of immune-related genes. Highlights: Nucleotides administration increased BW, ADG and FI. Nucleotides did not affect inflammatory and immune response.